2000
DOI: 10.1136/qhc.9.4.257
|View full text |Cite
|
Sign up to set email alerts
|

Complications of diabetes: renal disease and promotion of self-management

Abstract: A Melville, R Richardson, D Lister-Sharp, A McIntoshThis paper is an edited version of EVective Health Care volume 6 number 1, 1 which summarises information originally derived from systematic reviews undertaken to inform national clinical practice guidelines, 2 3 supplemented and re-analysed by the NHS Centre for Reviews and Dissemination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 93 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Therefore, we sequenced the entire coding sequence and exon/intron boundaries of the Hnf-1 β gene, which is responsible for MODY5 exhibiting diabetes and renal malformation in humans, and found no mutation in the Hnf-1 β gene of affected rats in the DEK strain (data not shown). DN is one of the complications in diabetes and a leading cause of chronic kidney diseases in humans [34]. To date, various DN animal models have been studied to elucidate the mechanisms and genetic factors involved in the development and progression of DN [13, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we sequenced the entire coding sequence and exon/intron boundaries of the Hnf-1 β gene, which is responsible for MODY5 exhibiting diabetes and renal malformation in humans, and found no mutation in the Hnf-1 β gene of affected rats in the DEK strain (data not shown). DN is one of the complications in diabetes and a leading cause of chronic kidney diseases in humans [34]. To date, various DN animal models have been studied to elucidate the mechanisms and genetic factors involved in the development and progression of DN [13, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Self-care education has been shown to improve laboratory data in several chronic diseases [10, 11]. However, one study in Japanese patients with renal diseases showed that scores for dietary self-assessment did not match with actual data for the serum urea nitrogen/urea creatinine ratio.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of interventions aimed at promoting self-management have been shown to lead to improved glycaemic control, weight loss and lower BP, but generally the effects are small 15 and there is no evidence of longterm benefits. Another review of RCTs of selfmonitoring in diabetes 16 showed no improvements in blood glucose levels in those who self monitor.…”
Section: Discussionmentioning
confidence: 99%